(untitled) (AmS-Skrifter, 2020)
Trade from 1400 onwards had an impact upon the North Atlantic region quite out of proportion to its volume. The opening of a ready market for dried fish, in particular, but also cloth, train oil and sulphur encouraged the production for export on a much larger scale than before. In return, a greater range of finished goods and raw materials was supplied by German merchants. Initially, trade was channelled through Bergen, but this system broke down, largely because English merchants sailed to Iceland. From the 1470s onwards, the number of German ships travelling to Iceland and Shetland increased. The Danish government struggled to control the trade in their North Atlantic territories, but first in the Faroes and later in Iceland, they sought to impose greater restrictions on foreign merchants. The Danes licensed ships to trade at certain ports and from 1601 attempted to restrict the trade to their own merchants. The introduction summarizes the history of German trade in the North Atlantic, and outlines its economic and cultural impacts.